Micro Surfacing Asphalt Pavement as a Mitigation Measure at Accident’s Prone Area along East Coast Expressway Phase 2 (ECE 2) - Abdul Kadir, A.I.; Rais, N.M.; Mohd-Towel, R. (Journal of the Society of Automotive Engineers Malaysia, 2020)
The condition of pavement surface is an essential factor to be considered in mitigation of accidents in highways, as it is in direct contact with users' vehicles, especially in terms of quality of driving, skid resistance and friction. Lack of surface pavement maintenance may lead to accidents, and if taken for granted, it may witness high accident fatalities in the expressways. If the cause of the accidents happening on the roads is due to engineering factors, then adequate mitigation measures should be undertaken to avoid further tragedies from happening. One way of mitigating the accidents on highways is by conducting periodic maintenance of the roads and related highway infrastructure. Micro- surfacing is one of the potential measures, developed from a slurry seal technique. It is the process of applying a mixture of polymer modified bitumen emulsion with 8.0 mm chipping, quarry dust, cement, additives and water on an existing asphalt pavement surface. The current study was carried out to evaluate the performance of micro-surfacing as a mitigation measure, applied on the accident-prone pavement areas along the East Coast Expressway Phase 2 (ECE2). The Portable Pendulum Tester was used to evaluate the skid resistance performance while the texture depth of micro-surfacing was measured using the Sand Patch Test. The results showed tremendous improvement in the skid resistance and texture depth after the application of micro-surfacing. The number of accidents also reduced after the application of micro-surfacing asphalt pavement as a mitigation measure at the identified accident-prone areas along ECE2. Thus, the study confirmed that micro-surfacing asphalt pavement was effective in mitigating the accidents in accident-prone areas along ECE2.